Development and application of oncolytic viruses as the nemesis of tumor cells - Zhu, Xiao; Fan, Chenyang; Xiong, Zhuolong; Chen, Mingwei; Li, Zesong; Tao, Tao; Liu, Xiuqing (Frontiers in Microbiology, 2023)
Viruses and tumors are two pathologies that negatively impact human health, but what occurs when a virus encounters a tumor? A global consensus among cancer patients suggests that surgical resection, chemotherapy, radiotherapy, and other methods are the primary means to combat cancer. However, with the innovation and development of biomedical technology, tumor biotherapy (immunotherapy, molecular targeted therapy, gene therapy, oncolytic virus therapy, etc.) has emerged as an alternative treatment for malignant tumors. Oncolytic viruses possess numerous anti-tumor properties, such as directly lysing tumor cells, activating anti-tumor immune responses, and improving the tumor microenvironment. Compared to traditional immunotherapy, oncolytic virus therapy offers advantages including high killing efficiency, precise targeting, and minimal side effects. Although oncolytic virus (OV) therapy was introduced as a novel approach to tumor treatment in the 19th century, its efficacy was suboptimal, limiting its widespread application. However, since the U.S. Food and Drug Administration (FDA) approved the first OV therapy drug, T-VEC, in 2015, interest in OV has grown significantly. In recent years, oncolytic virus therapy has shown increasingly promising application prospects and has become a major research focus in the field of cancer treatment. This article reviews the development, classification, and research progress of oncolytic viruses, as well as their mechanisms of action, therapeutic methods, and routes of administration.